Rhétorique et cognition - Rhetoric and Cognition. Perspectives théoriques et stratégies persuasives- Theoretical Perspectives and Persuasive Strategies - Oswald, Steve; Herman, Thierry (Sciences pour la Communication, 2014)
This volume gathers contributions from two disciplines which have much to gain from one another - rhetoric and cognitive science - as they both have much to say in the broad realm of argumentation studies. This collection neither condemns the fallacious effects of specific argument schemes nor adds yet another layer to fallacy criticism, but studies how argumentation and fallacies work, hic et nunc. What are the linguistic and cognitive mechanisms behind the «performance » of fallacious arguments? How do rhetorical strategies work at the interface of cognition, language science and society?